Wpływ pandemii COVID-19 na eksponowanie wartości witalnych w reklamach telewizyjnych (marzec-czerwiec 2020) = Coronavirus pandemic impact on vital values displayed in TV commercials (March-June 2020) - Burska, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article aims to analyse TV commercials referring to social isolation in the spring of 2020 during the COVID-19 pandemic from an axiological perspective. The author is trying to investigate the verbal and non-verbal means by which the vital values were exposed. The material consists of 52 advertising spots broadcast emitted on Polish television.
Keywords: reklama; wartości witalne; aksjologia; życie; zdrowie; pandemia; advertising; vital values; axiology; life; health; pandemic